Bioinformatic Approach to Unveil Key Differentially Expressed Proteins in Human Sperm After Slow and Rapid Cryopreservation - Corda, Pedro O.; Silva, Joana Vieira; Pereira, Sara C.; Barros, Alberto; Alves, Marco G.; Fardilha, Margarida (Frontiers in Cell and Developmental Biology, 2022)
Currently, two conventional freezing techniques are used in sperm cryopreservation: slow freezing (SF) and rapid freezing (RF). Despite the protocolar improvements, cryopreservation still induces significant alterations in spermatozoon that are poorly understood. Here, available proteomic data from human cryopreserved sperm was analyzed through bioinformatic tools to unveil key differentially expressed proteins (DEPs) that can be used as modulation targets or quality markers. From the included proteomic studies, 160 and 555 DEPs were collected for SF and RF groups, respectively. For each group, an integrative network was constructed using gene ontology and protein-protein interaction data to identify key DEPs. Among them, Arylsulfatase A (ARSA) was highlighted in both freezing networks, and low ARSA levels have been associated with poor-sperm quality. Thus, ARSA was selected for further experimental investigation and its levels were assessed in cryopreserved samples by western blot. ARSA levels were significantly decreased in RF and SF samples ( 31.97% and 39.28%, respectively). The bioinformatic analysis also revealed that the DEPs were strongly associated with proteasomal and translation pathways. The purposed bioinformatic approach allowed the identification of potential key DEPs in freeze-thawed human spermatozoa. ARSA has the potential to be used as a marker to assess sperm quality after cryopreservation.